2020
DOI: 10.1002/ange.201915949
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Axially Chiral Styrenes through Pd‐Catalyzed Asymmetric C−H Olefination Enabled by an Amino Amide Transient Directing Group

Abstract: The atroposelective synthesis of axially chiral styrenes remains a formidable challenge due to their relatively lower rotational barriers compared to the biaryl atropoisomers. Herein, we describe the construction of axially chiral styrenes through PdII‐catalyzed atroposelective C−H olefination, using a bulky amino amide as a transient chiral auxiliary. Various axially chiral styrenes were produced with good yields and high enantioselectivity (up to 95 % yield and 99 % ee). Carboxylic acid derivatives of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…In 2021, Lin and co-workers established a chiral phosphoric acid catalyzed a highly regio-, diastereo-, and enantioselective dearomatization reaction of 1-substituted 2-naphthols (53) and β,γ-alkynyl-α-imino esters (48). The highly functionalized naphthalenone derivatives (54) with allene moiety, exhibiting both a quaternary stereocenter and axial chirality, were obtained in good yields (up to 82%) with high diastereoselectivities (up to >99:1 dr) and enantioselectivities (up to 96% ee) (Scheme 16). Control experiments showed that high to excellent stereoselectivity is the result of a dual hydrogen bonding interaction between substrates and chiral phosphoric acid, with the substituent at the 1-position of 2-naphthol playing a key role in controlling regioselectivity.…”
Section: βγ-Alkynyl-α-iminomentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Lin and co-workers established a chiral phosphoric acid catalyzed a highly regio-, diastereo-, and enantioselective dearomatization reaction of 1-substituted 2-naphthols (53) and β,γ-alkynyl-α-imino esters (48). The highly functionalized naphthalenone derivatives (54) with allene moiety, exhibiting both a quaternary stereocenter and axial chirality, were obtained in good yields (up to 82%) with high diastereoselectivities (up to >99:1 dr) and enantioselectivities (up to 96% ee) (Scheme 16). Control experiments showed that high to excellent stereoselectivity is the result of a dual hydrogen bonding interaction between substrates and chiral phosphoric acid, with the substituent at the 1-position of 2-naphthol playing a key role in controlling regioselectivity.…”
Section: βγ-Alkynyl-α-iminomentioning
confidence: 99%
“…Motivated by elegant findings regarding the construction of axially chiral derivatives of styrene, Gu et al, Xu et al and Shi et al , reported palladium catalyzed enantioselective synthesis of axially chiral styrene derivatives. This advancement serves as a model for the atroposelective catalytic synthesis of derivatives of the axially chiral styrene.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Shi and co-workers reported a Pd-catalyzed enantioselective CÀH olefination for synthesis of axially chiral styrenes through cTDG strategy (Scheme 15). [39] Employing amino amide cTDG7 as transient Scheme 12. Pd-catalyzed atroposelective CÀH functionalization to access enantioenriched pentatomic biaryls using cTDG1 (Shi et al, 2019).…”
Section: Enantioselective Synthesis Of Molecules With Axial Chiralitymentioning
confidence: 99%
“…Pd-catalyzed enantioselective synthesis of axially chiral styrenes via cTDG strategy (Shi et al, 2020). [39] Angewandte Chemie crucial for the reactivity and enantioselectivity. Detailed investigation of the steric effect and pK a value of the acid additives disclosed that the weak and bulky aliphatic carboxylic acids exhibited better enantiocontrol.…”
Section: Enantioselective Synthesis Of Molecules With Planar Chiralitymentioning
confidence: 99%
“…5 The Shi and Wang groups reported the palladium-catalyzed atroposelective C−H alkenylation and alkynylation, respectively, where a palladacycle species was involved as a key intermediate (Scheme 1b). 6 Despite these impressive advances, the development of new methods involving conceptually innovative synthetic chemistry for their concise and efficient synthesis is highly desirable.…”
Section: ■ Introductionmentioning
confidence: 99%